ANALISIS KOMPETENSI GURU DALAM PENGGUNAAN MEDIA BELAJAR BERBASIS TEKNOLOGI DI SMP NEGERI 3 SITOLU ASLI - Zega, Serius; Lahagu, Arianto; Harefa, Yearning; Telaumbanua, Wahyutra Adilman (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze teacher competency in the use of technology-based learning media at SMP Negeri 3 Sitolu Ori. The background of this study is based on the importance of technology integration in the learning process to improve the effectiveness and efficiency of learning. Teachers as the spearhead of education are expected to have pedagogical, professional, social, and personality competencies that include the ability to operate and utilize learning technology. The research method used is a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The results show that the majority of teachers at SMP Negeri 3 Sitolu Ori have basic skills in using technological devices such as laptops, computers, projectors, and Microsoft Office applications, especially PowerPoint. However, the use of technology still faces several obstacles such as limited internet connection, lack of advanced technology training, and limited time in developing digital learning materials. In addition, the process of selecting learning media generally refers to the teaching module used, but not all teachers are able to optimally develop media independently. This study concludes that although most teachers have demonstrated basic skills in the use of technology-based media, competency improvement is still needed through continuous training and infrastructure support. The results of this study are expected to be a basis for schools and stakeholders to design programs to improve teacher professionalism in utilizing technology to achieve a more innovative and quality learning process.